2022
DOI: 10.3390/biology11071015
|View full text |Cite
|
Sign up to set email alerts
|

Goats as Valuable Animal Model to Test the Targeted Glutamate Supplementation upon Antral Follicle Number, Ovulation Rate, and LH-Pulsatility

Abstract: The potential effect of intravenous administration of glutamate on the ovarian activity and the LH secretion pattern, considering the anestrous yearling goat as an animal model, were assessed. In late April, yearling goats (n = 20) were randomly assigned to either (1) Glutamate supplemented (GLUT; n = 10, Live Weight (LW) = 29.6 ± 1.02 kg, Body Condition (BCS) = 3.4 ± 0.2 units; i.v. supplemented with 7 mg GLUT kg−1 LW) or (2) Non-supplemented (CONT; n = 10; LW = 29.2 ± 1.07 kg, BCS = 3.5 ± 0.2 units; i.v. sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Glutamate is an AA that acts as an excitatory neurotransmitter and stimulates GnRH production and release ( Chiang and Park, 2020 ). Under normal conditions, its activity is regulated by steroid hormones ( Barth et al, 2015 ; Porter et al, 2021 ), and supplementation with this amino acid has been shown to be effective in reducing the negative feedback effects of E2 ( Luna-García et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Glutamate is an AA that acts as an excitatory neurotransmitter and stimulates GnRH production and release ( Chiang and Park, 2020 ). Under normal conditions, its activity is regulated by steroid hormones ( Barth et al, 2015 ; Porter et al, 2021 ), and supplementation with this amino acid has been shown to be effective in reducing the negative feedback effects of E2 ( Luna-García et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…LW acted on the factors that promoted negative feedback, reducing its effects on the HPO axis, proving that glutamate intervenes as a signal for the beginning of the breeding season ( Meza-Herrera et al, 2020 ). As described by Luna-García et al (2022) , glutamate possibly acts by decreasing the action of dopamine on kisspeptin-producing neurons, activating the hypothalamic centers that synthesize and release GnRH, which promotes an increase in LH pulses and acts on ovarian activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations